2015
DOI: 10.1002/brb3.326
|View full text |Cite
|
Sign up to set email alerts
|

Isoniazid‐induced polyneuropathy in a tuberculosis patient – implication for individual risk stratification with genotyping?

Abstract: BackgroundDevelopment of polyneuropathy (PNP) under treatment for tuberculosis (TB), including isoniazid (INH), is a highly relevant adverse drug effect. The NAT2 acetylation status is a predictor of potential toxic effects of INH. The question as to whether individual risk stratification by genotyping is useful to avoid suffering of patients and to lower costs for the health care system is of considerable clinical importance.Case PresentationAfter drug treatment for TB, including INH, a 23-year-old man develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
0
12
0
2
Order By: Relevance
“…Drug-metabolizing enzymes are key factors that determine how drugs are metabolized in the body [39]. It has been reported that slow NAT2 acetylator genotypes and a CYP2E1 C1/C1 genotype can lead to an accumulation of toxic metabolites during the metabolism of INH in the liver [40]. It was also found that the quantities of toxic metabolites generated by breakdown of INH and RIF were significantly increased in patients with slow NAT2 acetylator genotypes [41].…”
Section: Discussionmentioning
confidence: 99%
“…Drug-metabolizing enzymes are key factors that determine how drugs are metabolized in the body [39]. It has been reported that slow NAT2 acetylator genotypes and a CYP2E1 C1/C1 genotype can lead to an accumulation of toxic metabolites during the metabolism of INH in the liver [40]. It was also found that the quantities of toxic metabolites generated by breakdown of INH and RIF were significantly increased in patients with slow NAT2 acetylator genotypes [41].…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration of INH and long-term therapy causes several serious side effects, which could even force treatment discontinuation. INH is known to cause hepatitis ( 26 ), hepatic injury and neuropsychiatric disturbances ( 27 ) including, among others, uncontrollable seizures ( 28 ) or polyneuropathy ( 29 ). The conventional oral route of INH administration causes periodic decrease of its concentration below the effective minimum inhibitory concentration (MIC), allowing MTB bacilli to develop resistance ( 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dari 33 pasien yang terlibat dalam penelitian ini sebanyak 22 pasien mengalami ROTD, distribusi ditunjukkan pada gambar 1, sedangkan Dari 33 responden ada beberapa pasien yang megalami satu macam ROTD saja, teapi juga terdapat beberapa pasien yang mengalami lebih dari 1 macam ROTD, distribusi digambarkan pada gambar 2. ROTD ke dua yang paling banyak dialami pasien berupa rasa nyeri baik pada persendian, kepala, kram pada kaki, maupun terjadinya kesemutan , gejala tersebut dapat merupakan gejala awal timbulnya neuritis 4 , yang dapat disebabkan oleh obat Isoniazid 5 , dan berkaitan dengan terjadinya interaksi antara isoniazid dengan vitamin B6 sehingga terjadi penurunan jumlah vitamin B6 yang diperlukan oleh system syaraf dalam tubuh 7 .Pada kasus ini, meskipun gejala gastrointestinal yang terjadi dapat merupakan bagian dari gejala awal gangguan hepar namun kejadian (hepatotoksisitas) yang dikonfirmasi dengan tanda klinis dan pemeriksaan laboratorium berupa peningkatan AST/ALT tidak ditemukan dalam kasus ini. ROTD berupa ruam kulit dan gatal terjadi pada 3 kasus dari 33 pasien, meskipun kasus ini jarang terjadi namun termasuk dalam ROTD mayor, pirazinamid adalah salah satu obat yang dapat menyebabkan gangguan kulit berupa exanthema dan berkaitan dengan mekanisme alergi 8 .…”
Section: B Distribusi Pasien Berdasar Jumlah Dan Jenis Rotdunclassified